A new tool for measuring anti-doping attitudes in elite athletes: The anti-doping programme evaluation questionnaire - Lamberti, N.; Malagoni, A. M.; Felisatti, M.; Caracciolo, S.; Resch, N.; Litmanen, H.; Dal Follo, D.; Jeannier, P.; Zhukovskaja, L.; Carrabre, J. E.; Manfredini, F. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Background: The international federations, which have progressively strengthened the anti-doping programs, with new duties for athletes, lack any feedback in terms of acceptance and satisfaction of the anti-doping actions from athletes themselves. The project aimed i) to develop, an anonymous self-administered tool measuring elite athletes` attitudes on international anti-doping interventions, and ii) as first implementation, to survey anti-doping attitudes among top biathletes. Methods In the absence of available literature, relevant topics and items were identified. The preliminary English version of the anti-doping program evaluation questionnaire (APPROVE) was developed, translated (German, Russian and Italian) and distributed during an international biathlon event to a sample group for validation. The questionnaire`s final structure was determined by factor analysis. Construct validity was explored by correlation with a single item of satisfaction and also internal consistency and test-retest reliability were evaluated. A cross-sectional evaluation of the anti-doping attitude among elite biathletes was performed by administering APPROVE final validated version. Results Sixty-two subjects participated in the validation phase. The final version of APPROVE included: i) a Demographics section, ii) an Awareness section measuring respondents` knowledge of the anti-doping rules, and iii) an Anti-doping attitude section, including four 9-item domains (Safety, Confidence, Acceptance and Satisfaction) exploring athletes` perceived protection against cheating, confidence in competition fairness, acceptance of and satisfaction with anti-doping actions. APPROVE had construct validity, good internal consistency and significant-acceptable test-retest reliability. Two hundred forty-four biathletes participated in the survey (44,4% of response rate) with the Awareness score insufficient for 9% of them. A positive attitude was observed (ADOPT score: 64.9), with good-excellent scores for 74% of the athletes. The score domains were significantly lower for Safety (58.2) and higher for Satisfaction (70.8). Conclusions APPROVE, not being a sport specific questionnaire, allows a multi-faceted evaluation of the anti-doping attitude in sport and of the impact of anti-doping strategies on athletes. Its first implementation among top biathletes outlines a positive attitude towards the present anti-doping interventions, and the willing to accept the related restrictions to be protected against cheating.